Analisis Prediksi Kebangkrutan Menggunakan Model Altman, Springate, Grover, dan Zmijewski pada Perusahaan Sektor Consumer Cyclicals - Artini, Ni Luh Putu Santi; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2024)
The bankruptcy prediction model is useful for knowing the condition of the company. The aim of this research is to obtain empirical evidence regarding consumer cyclical sector companies that are predicted to go bankrupt using the Altman, Springate, Grover, and Zmijewski models, as well as the differences between the four models. The sample determination method uses a purposive sampling method. The data used is secondary data in the form of financial reports for 2020-2021 obtained from the Indonesian Stock Exchange. The analysis technique uses the formula for each model, the Mann-Whitney test and the Kruskal-Wallis test. The research results show that there are companies in the consumer cyclicals sector that are predicted to go bankrupt using the Altman, Springate, Grover, and Zmijewski models, and there are differences between the four models. The results of this research provide information to company management to evaluate company performance, especially in consumer cyclical sector companies that are predicted to experience bankruptcy. Keywords: Bankruptcy; Altman; Springate; Grover; Zmijewski